Metformin Enhances B Cell Function and Antibody Responses of Elderly Individuals With Type-2 Diabetes Mellitus - Frasca, Daniela; Diaz, Alain; Romero, Maria; Blomberg, Bonnie B. (Frontiers in Aging, 2021)
Our previous work has shown that young and elderly patients with Type-2 Diabetes Mellitus (T2DM) treated with Metformin have optimal B cell function and serum antibodies specific for the seasonal influenza vaccine. In this paper, we have evaluated B cell function and the metabolic requirements of B cell antibody responses in elderly T2DM patients (ET2DM) taking or not Metformin, and compared to those of healthy elderly (EH) and healthy young (YH) individuals. Results show that Metformin significantly increases in vivo B cell function, measured by influenza vaccine-specific serum antibodies, in ET2DM patients to the levels observed in EH and more importantly in YH individuals. Metformin also decreases the frequencies of pro-inflammatory B cell subsets, as well as intrinsic inflammation and metabolic requirements of peripheral B cells from ET2DM. This hyper-metabolic phenotype of B cells from ET2DM is needed to support intrinsic inflammation, measured by the expression of transcripts for markers of the senescence-associated secretory phenotype (SASP), and the secretion of autoimmune antibodies. Importantly, B cell function in ET2DM patients taking Metformin is not only increased as compared to that in ET2DM patients not taking Metformin, but is comparable to B cell function measured in YH individuals. These results altogether strongly support the anti-aging effects of Metformin on humoral immunity.